Design and implementation of data collection module for WSN application - Markova, Valentina; Trifonova, Teodora; Draganov, Venceslav (International Journal of Engineering and Technology, 2015)
This paper presents the design and implementation of universal low cost data collection module (DCM), which is an essential part of remote monitoring system based on wireless sensor network. The proposed module expands the capabilities of a measuring node for collecting data from greater number of sensors. The DCM includes four parts: one group multiplexers for data acquisition, second group multiplexers for power management, voltage to current converters and DC/DC converters. The universal DC/DC converters provide autonomous power supply for the sensors and the multiplexers, which can be turned on or off for a certain period of time. The data collecting, monitoring and logging functions are realized through a LabVIEW project.The proper operation and the reliable performance of the system were proved by practical experiment. The proposed module makes the WSN-based system a versatile solution for a variety of monitoring applications.